Effects of Labour Migration on Poverty and Agricultural Growth in Nepal - Pant, Krishna P (Journal of Agriculture and Environment, 2013)
Increasing labour shortage in agriculture sector and contribution of remittance on poverty reduction has raised the importance of studies on employment, poverty and agricultural growth nexus. The study explores the effects of foreign employment on poverty and agricultural growth. The study using time series secondary data for 19 years fitted econometric models at sectoral level to establish the effects of migration on poverty and agricultural production. It also compares agricultural output elasticity of foreign employment and assesses the role of foreign employment on the relationships between growth, poverty and agricultural development. The results show that migration decreases poverty and at the same time decreases agriculture production. But, the decrease in agriculture gross domestic product per unit of labour migrated is smaller than the per capita remittance. The study does not dwell on the social and cultural effects of the labour migration. The results will be useful for decision makers to devise sound policies on migration, poverty and agricultural development.